2019
DOI: 10.1097/mao.0000000000002364
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Postoperative Opioid Use in Otologic Surgery

Abstract: Objective: To prospectively evaluate opioid consumption following adult outpatient otologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 15 publications
3
35
3
Order By: Relevance
“…The average opioid prescription consisted of ~41 pills (5-mg hydrocodone equivalents), while previous studies have shown that <10 pills were consumed after otologic surgery. 6-8 This study also revealed clinical and sociodemographic factors that contribute to high opioid prescriptions.…”
Section: Discussionmentioning
confidence: 64%
“…The average opioid prescription consisted of ~41 pills (5-mg hydrocodone equivalents), while previous studies have shown that <10 pills were consumed after otologic surgery. 6-8 This study also revealed clinical and sociodemographic factors that contribute to high opioid prescriptions.…”
Section: Discussionmentioning
confidence: 64%
“…There were 24 studies identified, including 6 RCTs, 13 prospective observational studies, and 5 retrospective observational studies, that described mean or median consumption with either the standard deviation or the 75th percentile. 147,152,153,164-185 Opioid consumption was initially converted into morphine milligram equivalent (MME) units 186 ( Table 15 ), and individual procedures were compared. MME is a value assigned to compare the opioid dosage equivalency to another opioid.…”
Section: Key Action Statementsmentioning
confidence: 99%
“…164 c Two studies reported opioid consumption in aggregate for various otology procedures (tympanoplasty, tympanomastoidectomy, cochlear implantation, and stapedectomy), and only transcanal procedures were found to have lower opioid consumption. 176,177 d Data represent the 75th percentile. No ~85th percentile data were available for these procedures. …”
Section: Key Action Statementsmentioning
confidence: 99%
“…Second, claims for opioid prescriptions filled at outpatient pharmacies were used to proxy prescriber behavior. This proxy underestimates opioid prescriptions; one prior study showed that 15% of patients who received an opioid prescription did not fill it 33 . As the study included only privately insured children, results may not generalize to publicly insured children.…”
Section: Discussionmentioning
confidence: 96%